수정된 방사 에너지법과 단파장 영역 보정법을 이용한 파랑 중 부가저항 추정에 관한 연구 - 오승훈(Seunghoon Oh); 양진호(Jinho Yang) (大韓造船學會 論文集, 2016)
A simple calculation tool for added resistance in waves is developed to utilize for initial design or embedded module for navigation support system. In order to select an appropriate calculation method for added resistance in waves, three methods (drift method, integrated pressure method, radiated energy method) based on strip method are applied to Wigley I and KVLCC2. The methods for added resistance in waves give the underestimated results because it is difficult to consider nonlinear effects due to reflected wave. We apply asymptotic (Faltinsen's method) and empirical formula (NMRI's method) to improve the accuracy for short wave length region. In comparison with experimental results, the combination of radiated energy method and short wave correction method of NMRI is the most reasonable. However, a simple sum of results calculated by two methods gives rise to the overestimation of added resistance for short wave length region because added resistance of radiated energy method exits in total reflection region. To overcome this problem, modified radiated energy method is proposed using correction coefficient defined by reflection coefficient of NMRI's method. Finally, added resistance in regular waves is composed of added resistance of modified radiated energy method and that of short wave correction method of NMRI. Estimated added resistance in regular waves is validated by comparison with experimental results of other research groups.